Análise processual da responsabilidade penal da pessoa jurídica por crimes ambientais na cidade de Manaus - Costa, Ruan Patrick Teixeira da (2024)
The present study aims to analyze the issue of criminal liability of legal entities for environmental crimes in the city of Manaus, using as a basis legal proceedings in progress in the District of Manaus with descriptions and analyzes relating to the procedural progress. To better support the dissertation, a historical and geographical contextualization of the city of Manauara was made, using academic texts about the first inhabitants of the region, the Manáos, an indigenous group that is now extinct, as well as studies on the implementation of public policies that occurred during the period at the height of rubber exploitation, the creation of the Free Trade Zone and current issues such as the creation of PROSAMIM and the floating issue. As the dissertation progressed, the theme of the principles of the environmental field was discussed, which served as the basis for the development of this work, as well as the theme of responsibility for damage to the environment (a fundamental, diffuse, and transgenerational right, which has constitutional and legal protection) and its possibilities, with greater emphasis on the criminal scope and its application to companies, which, through their activities, cause damage to the environment. The final and not even important chapter of the research dealt with the analysis of legal proceedings in progress in the capital of Amazonas, in which it was verified the possibility of imputing criminal conduct set out in the law of environmental crimes to legal entities, due to accidents caused to biodiversity in the Amazon region, especially in the capital of Amazonas, an economic, political and strategic center, which has great business activity and various issues related to biodiversity.